Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Kelas V SD Swasta GKPS 2 Merek Raya Pada Mata Pelajaran IPA - Imelda Sabrina Sibarani; Yenni Sibue; Nenny Wati Harianja; Ruth Ompusunggu (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This type of research is quantitative, namely pre-experimental design or often referred to as Quasi Experiment (pretend experiment) with the One Group pretest and posttest method. This research aims to see whether there is an influence of the jigsaw learning model on student learning outcomes. The population in this study were all students at GKPS 2 Brand Raya Private Elementary School and the sample in this study was class V students, totaling 14 girls and 14 boys. The sampling technique used was cluster sampling with two research variables, namely: the independent variable (x ) namely the jigsaw type cooperative learning model and the independent variable (y) namely student learning outcomes. The data collection technique is by tests and will take place in the 2024/2025 academic year. There is an influence of the jigsaw type cooperative learning model on the learning outcomes of sub-theme 1 class V students at GKPS 2 Brand Raya Private Elementary School.